The great Chinese inequality turnaround - Ravi Kanbur; Yue Wang; Xiaobo Zhang (Bank of Finland, Institute for Economies in Transition (BOFIT), 2017)
China's high income and wealth inequality has long attracted the interest of policymakers and re-searchers, yet surprisingly little has been done since 2010 on inequality trends. Given China's evolving economic structure and the government's adoption of new policy tools in recent years, we revisit the latest data on Chinese inequality and assess the impacts of economic and policy changes on income distribution. After a quarter century of rapid, sustained increase, we see Chinese inequality plateauing and even diminishing. To verify this finding, we draw upon a range of data sources and measures of inequality. We examine inequality trends through decomposition by income source and population subgroups, and consider possible explanations such as policy shifts and structural trans-formation of the Chinese economy. The findings suggest that the narrative on Chinese inequality today should focus on clarifying the factors driving this apparent inequality turnaround.
URN:NBN:fi:bof-201705031257
Keywords: D31; D63; O15; O53; 330